2017
DOI: 10.12991/marupj.300924
|View full text |Cite
|
Sign up to set email alerts
|

New-generation Jeffamine® D230 core amine, TRIS and carboxylterminated PAMAM dendrimers: Synthesis, characterization and the solubility application for a model NSAID drug Ibuprofen

Abstract: Many therapeutically active drugs are poor water soluble and, therefore, bioavailability of these molecules in the living cells is low and a major problem. In this study, new-generation Jeffamine ® D230 core, amine (NH 2 ), Tris(hydroxymethyl) aminomethane (TRIS), and carboxyl (COOH) terminated poly(amidoamine) PAMAM dendrimers (PAMAMs) were synthesized. Synthesized new-generation PAMAMs were characterized by 1 H NMR, 13 C NMR, ATR-FTIR, and investigated as solubility enhancer of a sample non-steroidal anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
2
0
7
Order By: Relevance
“…For example, Javan and coworkers [41] introduced a jeffamine chemical functionalization in hyaluronic acid-based hydrogels to formulate a prolonged and sustained drug release and reduce the number of hydrogel injections: in vivo studies showed the efficiency of this material thanks to the improved biocompatibility and no signal of cell viability reduction. Similar biocompatibility aims were achieved in other works: the jeffamine was used as monomer to preserve some physico-mechanical properties, blood compatibility and cargo release [42][43][44][45], as copolymer with acrylamides derivatives to design 3D scaffolds able to modulate the lower critical solution temperature (LCST) and internalize cells [46] or as cross-linker to satisfy the no-cytotoxicity criteria [47]. However, the evaluation of the polymer antimicrobial features and the design of a 3D scaffold able to preserve them is not widely investigated.…”
Section: The Role Of the Physico-chemical Transitionmentioning
confidence: 69%
“…For example, Javan and coworkers [41] introduced a jeffamine chemical functionalization in hyaluronic acid-based hydrogels to formulate a prolonged and sustained drug release and reduce the number of hydrogel injections: in vivo studies showed the efficiency of this material thanks to the improved biocompatibility and no signal of cell viability reduction. Similar biocompatibility aims were achieved in other works: the jeffamine was used as monomer to preserve some physico-mechanical properties, blood compatibility and cargo release [42][43][44][45], as copolymer with acrylamides derivatives to design 3D scaffolds able to modulate the lower critical solution temperature (LCST) and internalize cells [46] or as cross-linker to satisfy the no-cytotoxicity criteria [47]. However, the evaluation of the polymer antimicrobial features and the design of a 3D scaffold able to preserve them is not widely investigated.…”
Section: The Role Of the Physico-chemical Transitionmentioning
confidence: 69%
“…Son çalışmamızda TREN (T) ve Jeffamine® D230 (D) çekirdekli yüksek jenerasyonlu PAMAM türü dendrimer sentezini ve karakterizasyonu gösterildi (Ertürk et al, 2017b;Gürbüz et al, 2017). Bu çalışmada (T) ve (D) çekirdekli ester sonlu PAMAM dendrimerin (D4.5.COOCH 3 ve T4.5.COOCH 3 ) ~ % 10 oranında PEG bisamin ile modifiye edildikten sonra geriye kalan ester grupları hidroliz edilerek çözünürlüğü çok düşük olmasından dolayı, kanın içinde hızlı emilmemesi, plazma proteinleriyle yetersiz ilişkisi ve birçok yan etkisi (ateş, deri döküntüsü, hematolojik bozukluk, vb.)…”
Section: Dendrimerlerinunclassified
“…SMZ-PAMAM dendrimer kompleksleri önceki çalışmalarımıza göre hazırlandı (Ertürk et al, 2017b(Ertürk et al, , 2017aGürbüz et al, 2017). 1:1 molar oranında SMZ-PAMAM karışımları metanolde çözüldü.…”
Section: Smz-pamam Dendrimer Komplekslerin Hazırlanmasıunclassified
See 1 more Smart Citation
“…KETO-PAMAM dendrimer kompleksleri önceki çalışmalarımıza göre hazırlandı [21,25,26]. 1:1 molar oranında KETO-PAMAM karışımları metanol'de çözüldü.…”
Section: İlaç-pamam Dendrimer Komplekslerin Hazırlanmasıunclassified